बघेली कथाएँ : बघेलखण्ड जनपद की लोककथा - Gautam, Suryanarayan (Aadivasi Lok Kala evm Boli Vikas Academy Madhya Pradesh Sanskriti Parishad, 2015)
The book is a collection of Bagheli folk tales which have moral values.
Bagheli Kathayen: Baghelkhand Janpad Ki Lok Katha
Keywords: Folk Culture; Hindi; Bagheli